Prevalence of RPGR-mutated X-linked retinitis pigmentosa among males. (3rd September 2022) - Vinikoor-Imler, Lisa C.; Simpson, Chris; Narayanan, Divya; Abbasi, Saad; Lally, Cathy
ABSTRACT: Background: X-linked retinitis pigmentosa (XLRP) is a rare inherited retinal disease predominantly affecting males. Materials and methods: A comprehensive literature review was conducted to determine the prevalence of retinitis pigmentosa GTPase regulator (RPGR) -mutated XLRP. Identified studies were used to estimate four components among males: the prevalence of retinitis pigmentosa (RP), the proportion of RP that was X-linked, the proportion of misclassified inheritance type among RP cases, and the proportion of XLRP that was RPGR -mutated. Studies providing a direct estimate of XLRP prevalence were also included. The components' sample size-weighted averages were combined to determine an overall prevalence estimate. Results: The prevalence of XLRP was estimated to be between 2.7–3.5 per 100, 000 males in the US, Europe, and Australia. After correction for misclassification, the prevalence increased to 4.0–5.2 per 100, 000 males. Finally, the proportion of XLRP cases due to RPGR mutations was applied, resulting in an RPGR -mutated XLRP estimate of 3.4–4.4 per 100, 000 males. Studies from other countries were consistent with the results for the overall XLRP prevalence but were not included in the final calculation because of regional variations and lack of detailed information. Conclusions: These findings address an important gap in the understanding of RPGR -mutated XLRP by summarizing the global burden of this condition.